Estimating the Bearing Capacity of a Square Footing on a Geogrid-Stabilised Granular Layer over Clay Using the Finite Element Method - Boon Tiong Chua; Kali Prasad Nepal; Hossam Abuel-Naga (Advances in Civil Engineering, 2023)
The bearing capacity of a square footing on an unstabilised and geogrid-stabilised granular layer over clay is estimated using finite element techniques in ABAQUS (a commercial finite element software). The model incorporates a range of soil parameters and layer thicknesses. The two-layered soil system in the model assumes a strong upper granular layer and a weak lower clay layer. The parametric results of the finite element analyses are used to develop design curves with dimensionless parameters in terms of linear gradient and the ratio of the undrained shear strength of clay to the effective vertical stress of the granular layer. The design curves are compared with the published results in the literature and found to be promising. The developed design curves are applied to estimate the minimum thickness of the granular layer and are compared with other existing methods. This application illustrates the simplicity of the proposed technique and reveals that the proposed approach yields a reasonable prediction for the bearing capacity when compared with other established methods.